SCIENTIFIC AND SCIENTIFIC-PRODUCTION ACTIVITY OF NATIONAL RESEARCH UNIVERSITY - Ilnur A. Abdullin; Aleksandr F. Dresvyannikov (Moscow Polytechnic University, 2016)
The article describes the main aspects of the scientific and scientific-production activities of Kazan National Research Technological University. It is shown that the strategic goal is to maximize KNRTU competitive advantages in the field of deep processing of raw materials, technology development of new materials for civil and defense values. The paper stresses the importance and the need for development of engineering activity in order to form an integrated system "science - education - production".